Aboveground Phenology of Tectona philippinensis Benth. & Hook.f.: Insights into Its Adaptive Mechanisms - Hernandez, Jonathan Ogayon (Department of Forestry, Faculty of Agriculture, University of Lampung, 2024)
The present study investigated the leaf flushing, leaf shedding, flowering, and fruiting cycles in Tectona philippinensis Benth. & Hook.f., shedding light on its adaptation mechanisms for reproductive success and survival. A plotless inventory of tree individuals was undertaken from pre-determined observation points from January 2022 to February 2023 in Lobo, Batangas. All 430 sampled trees exhibited leaf shedding and leaf flushing, while flowering and fruiting events were observed in only 201 and 133 trees, respectively. Major leaf flushing of trees was observed in mid-October, and they generally shed in summer (peak: March). Trees bloomed in early May and reached its peak in June. Fruiting occurred in the wet season (early July to September). There was a general pattern of leaf shedding, flushing, and varying flowering and fruiting cycles, indicating adaptability to environmental changes. The species also exhibited a significant time lag (7–8 months) between leaf flushing and shedding, potentially serving as adaptive features to promote reproductive success and survival in response to changing environmental conditions. Thus, the aboveground phenology of T. philippinensis may vary depending on environmental conditions. The findings are relevant for developing in-situ conservation strategies for the species. Keywords: flowering, flushing, Lamiaceae, phenological inventory, Shedding